The Hispanic-American Universitary Federation in Madrid - Carreño, Luciana (CIAN-Revista de Historia de las Universidades, 2013)
Throughout the 1920’s the Hispanic-American Universitary Federation established itself as a student organization that brought together a group of young Latin-Americans in Madrid who came to Europe to continue with their universitary studies andwere ether interested in the European cultural circles of the time or fleeing from political prohibitions in their countries of origin. Relations with Spanish students and authorities during the dictatorial times; student practices concerning the organization of the entity and propagandistic diffusion; references to the political activity of Latin-American student organizations are some of the matters that will be discussed in this article which intends to inquire into this students federation’s first years.
Keywords: Hispanic-American Universitary Federation; Spanish American; student associations; university; latin -American students